Design and analysis of multiband isolation RF switch using transmission line stub resonators for WiMAX and LTE applications - Saghir Zobilah, Abdullah Mohammed (2017)
In the area of multiband wireless communications, the development of multiband RF front-end sub-components (e.g. amplifiers, filters, switches and antennas) are highly desired, and they were developed to support several RF front-end systems. High isolation between transmitter and receiver in the RF front-end is one of the key parameters in RF switch design, especially for high power applications such as base stations and wireless infrastructure. High isolation between the RF front-end’s transmitter and receiver is required to minimize any high RF power leakage that could distort active circuits in the receiver, especially the low-noise amplifiers. Hence, this research proposes a multiband isolation RF switch as (Single Pole Double Throw (SPDT) and Double Pole Double Throw (DPDT)) design using switchable transmission line stub resonators for applications of Worldwide Interoperability for Microwave Access (WiMAX) and Long-Term Evolution (LTE) in 2.3 and 3.5 GHz bands. Clearly, a multiband isolation discrete RF switch was designed in two ways, fixed and selectable. The transmission line stub resonator used in this research work is an open stub resonator with quarter wave of the electrical length. The theory of the stub resonator is discussed using a simple mathematical model where it can be cascaded and resonated at 2.3 and 3.5 GHz. Moreover, the cascaded transmission line stub resonators can be reconfigured between allpass and bandstop responses using discrete PIN diodes. The key advantage of the proposed SPDT and DPDT with switchable transmission line stub resonators is a high isolation with minimum number of PIN diodes. As a result, the simulated and measured results showed less than 3 dB of insertion loss, greater than 10 dB of return loss and higher than 30 dB of isolation in 2.3 GHz and 3.5 GHz bands. Thus, the proposed design is suitable for high power applications with 1 Watt and 10 Watt transmits output. In addition, the selectable SPDT and DPDT switch show the best performance as they are able to operate with different frequencies using single hardware and thus, overcoming the interference issue.